SISTEM PELAYANAN BANTUAN MENTOR BIMBINGAN BELAJAR (BAMBIMBEL) BERBASIS WEB - Fadhli Ranuharja; Bayu Ramadhani Fajri; Agariadne Dwinggo Samala (Universitas Negeri Padang, 2020)
The existence of demands for the acceptance of new students by using the national selection exam of tertiary institutions in Indonesia, high school / vocational high school graduates are expected to master a number of basic subjects. Based on the primary data, the students’ interview in choosing the majors for college which was conducted in Senior High School / Vocational High School in Indonesia are insufficient for the students to take the national exam. The purpose of this study is to produce a service system in the form of giving the facilities for students to abilities in teaching practice and facilitate students who want to learn but having a financial issue. It is expected that with the assistance by student teacher, it will be easier for other students to understand and gain sort of interest in the study. Based on the observation, both from the point of view of college students and the point of view of high school / vocational high school students, then it is considered essential to create this service system. Learning with this tutoring facility is very effective because it directly encourages the students in the competency section that they do not fully understand with the help of tutors who have a better understanding. The method used is a web-based system design with UML modelling, using use case diagrams, activities, collaborations and class diagrams to plan the flow of data transactions that exist in the mentoring assistance service system of tutoring.